Optimalisasi Penggunaan Aplikasi Finetiks Untuk Mengurangi Doom Spending Pada Mahasiswa Melalui Edukasi Literasi Keuangan Digital - Hasanah, Naimatul; Badria, Nuril (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aimed to enhance digital financial literacy among university students and reduce doom spending behavior through the utilization of the Finetiks application. The activities were conducted in a structured and participatory manner, involving interactive training sessions, case study discussions, application usage simulations, and evaluations using pre-test and post-test instruments. A total of 35 students from various faculties at the Islamic University of Malang, including participants from the Entrepreneurship Program, Tax Center, and supported by the LPKIB (Entrepreneurship Development and Business Incubator Institute), actively engaged in the program. The pre-test results indicated that only 6% of participants could correctly identify the characteristics of doom spending, and only five students reported regularly recording their personal finances. Following the program, significant improvements were observed: 97% of participants answered correctly on the post-test and demonstrated behavioral changes such as tracking daily expenses and creating personal financial plans. These findings suggest that a technology-based educational approach using Finetiks is effective in fostering financial awareness, self-discipline, and healthy financial habits among university students.